(untitled) (The Research of Medical Science Review, 2024)
Background: Traumatic Brain Injury is actually a critical health issues to society because of the morbidity and mortality among the patients especially when the case is severe. Thus, proper management of TBI and prompt performance of surgical procedures are vital for enhancing patients’ quality of life. Monitoring of Intracranial Pressure (ICP) is an important procedure utilized in the management of severe TBI, since it gives important data directing surgical interventions. However, there is need to assess the efficiency of the information and incorporate standardized procedures for its application. Aim: The objectives of this research are to assess the quality of ICP monitoring in the management of severe TBI and to savoir the kind of decision-making that ICP monitoring can support for patients with TBI; to assess the correspondence of the ICP-guided surgery with the registered outcomes of patients; and to find out how adequately ICP measurement can be used to help the improvement of TBI clinical outcomes. Method: There was a prospective cohort study carried out involving patients diagnosed with severe TBI. The patients’ inclusion and exclusion criteria were used in the study while classifying them according to their demographic and clinical profiles. ICP monitoring was done with intraparenchymal data was obtained from records of the patients, operations, and assessments made after the operations. The outcomes included were deaths and the decompressive craniectomy (DC) these are the two main ones while others are the complications rate, the length of the hospital stay, among others. Statistical analysis was done through regressive and survival statistic with the use of analytical applications such as the SPSS and R. Results: The study concluded that ICP monitoring directly affected the choices of surgery plan that would increase the rate of early surgeries like decompressive craniectomy and hematoma evacuation. Primary outcomes of the study such as mortality and functional status at the end of the study were significantly better for the ICP-guided surgery group than in the patients who did not receive this intervention. There were mild differences, due to the subgroup analysis by age and gender, as well as the presence of co-morbidities. Some of the perceived difficulties and advantages of adopting ICP data for decision- making during surgery were captured through semiquantitative evaluation of the triangulated patients’ and health care providers’ data. Conclusion: More so, ICP monitoring is impactful in enhancing the surgical outcomes of patients having severe TBI through helping in determining the right surgical interventions at the right time. The findings of this study add to the knowledge of ICP monitoring in cases of TBI and reemphasise the role of including ICP during the management of these patients with a view of improving their outcomes. Further research has to target long-term follow-up results and the creation of new methods of surveillance.